Solving parallel machine scheduling problem with release dates using genetic algorithm - Suppiah, Yasothei; Angusamy, Ajitha; Wei Wei, Goh; bt Ismail, Noradzilah (International Journal of Engineering and Technology, 2018)
This research deals with a scheduling problem for parallel machines environment to minimize total weighted tardiness with the consideration of sequence dependent setup times and release dates. There are two research questions that need to be addressed: 1) How to allocate jobs on machines ?Â 2) How to sequence jobs on each machine? Therefore, this research aims to find an efficient solution method that answers the research questions with the goal of minimizing the total weighted tardiness with the presence of sequence dependent setup times. Due to the complexity of the problem at hand, the authors have developed genetic algorithm to find a solution to this problem. Furthermore, various dispatching rules were used to enhance the performance of the genetic algorithm in terms of the total weighted tardiness value.Â